2012
DOI: 10.3109/14653249.2011.605350
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a procedure to isolate viable bone marrow cells from the vertebrae of cadaveric organ donors for composite organ grafting

Abstract: Background aims Donor-derived vertebral bone marrow (BM) has been proposed to promote chimerism in solid organ transplantation with cadaveric organs. Reports of successful weaning from immunosuppression in patients receiving directed donor transplants in combination with donor BM or blood cells and novel peri-transplant immunosuppression has renewed interest in implementing similar protocols with cadaveric organs. Methods We performed six pre-clinical full-scale separations to adapt vertebral BM preparations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 18 publications
0
34
0
Order By: Relevance
“…[17][18][19] It has also been shown previously that split-thickness skin grafts could be allografted up to 3 weeks after death if stored at 4 C. 20 More recently, stem and adult cells have been isolated from post mortem brain, spinal cord, and retinal tissue. 3,[21][22][23] These findings showed that, due to the persistence of stem cells, cadaver tissue could be a potential abundant source of these cells. We are the first to report that viable CDCs can be isolated post mortem, in both humans and mice.…”
Section: Discussionmentioning
confidence: 84%
“…[17][18][19] It has also been shown previously that split-thickness skin grafts could be allografted up to 3 weeks after death if stored at 4 C. 20 More recently, stem and adult cells have been isolated from post mortem brain, spinal cord, and retinal tissue. 3,[21][22][23] These findings showed that, due to the persistence of stem cells, cadaver tissue could be a potential abundant source of these cells. We are the first to report that viable CDCs can be isolated post mortem, in both humans and mice.…”
Section: Discussionmentioning
confidence: 84%
“…The clinical transplantation protocol was approved by the University of Pittsburgh Internal Review Board. A total of nine vertebrae (Th8–L4) were harvested according to our published procedure [7]. VBs were rinsed with a saline–betadine solution and double-bagged with 2 l of sterile Custodiol ® preservation solution (Essential Pharmaceuticals, LLC, Newtown, PA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have expanded the use of this technique to hand and forelimb grafts [6], where the indication for transplantation is quality of life improvement and there is a pressing need to protect the patient from the risks of lifelong immunosuppression. In order to implement the Pittsburgh Protocol in this setting we preformed preclinical experiments to develop and validate a Good Manufacturing Practice (GMP)-compliant method for preparation of a cellular product from cadaveric vertebral bodies [7]. In this article, we describe the implementation of this methodology as a clinical protocol, and publish the full working procedure as Supplementary Material (see online at www.futuremedicine.com/doi/suppl/10.2217/RME.11.89).…”
mentioning
confidence: 99%
“…Novel immunomodulation protocols, such as infusion of donor derived bone marrow cells as used by the senior authors, further impact procurement logistics and need to be carefully considered. 12,36,37 Overall, the field of VCA is rapidly evolving, requiring further standardization, guidelines, more consistent reporting, and is ripe with opportunity to advance current practice and knowledge.…”
Section: Future Directionsmentioning
confidence: 99%